Lam Soon Edible Oils Sdn Bhd / Anis Insyirah Mahadi - Mahadi, Anis Insyirah (Faculty of Business and Management, 2023)
My memorable and enlightening 6-month industrial training began here at one of the well-established companies named Lam Soon Edible Oils Sdn. Bhd. It is located at Telok Panglima Garang, Selangor. There are many good memories and such an amazing journey for me. I have received many knowledge, new ideas, new perspectives, and many more. The duration of 6-month industrial training was one of my unforgettable journeys because I got to be in the Shipping Department and receive a supervisor named Madam Jamilah Binti Rahmat, who has 30 years of experience in this industry. Thus, I can know many things based on what they share on history too. Lam Soon Edible Oils Sdn. Bhd. (LSEO) is a subsidiary of Lam Soon (M) Bhd. that started in August 1950 in Singapore. It is one of the companies known for its Fast-Moving Consumer Goods (FMCG) products. It is a well-known company that manufactures, sells, and exports household and personal care products. For instance, Antabax shower cream, Buruh cooking oil, Labour dish paste, and others. The company can get customers’ hearts because the products use good ingredients, convenient and useful. The name Lam Soon actually has meaning behind it. The Lam Soon actually means big wok. Then, we will cook many types in this one big work together. Thus, this means we do together to achieve our target and become one of the most successful companies. However, even though Lam Soon Edible Oils Sdn. Bhd. is one of the stable companies, but still, we need to do SWOT Analysis to know better and improve more in the company. Strong brand recognition and strong market presence is the strength of the company. The weaknesses are an unfriendly M3 System, unorganized files, and outdated machine and insufficient equipment. Then, let’s take a look at the opportunity to make this company more successful. The opportunity is increased collaboration, an online shopping platform, and an eco-friendly office. The threats are stiff competition, monsoon season, and changing consumer preferences. Of course, every company has its competitor, but how they want to maintain success is the main point that we will explain more about below.